Phenolic and Antioxidant Diversity Among Fruit Species Grown in Turkey - ERCISLI, SEZAI; OZDEMIR, OZLEM; SENGUL, MEMNUNE; ORHAN, EMINE; GUNGOR, NEVA (Asian Journal of Chemistry, 2010)
To identify promising sources of antioxidants, 22 fruit species were studied for total phenolic contents and antioxidant activity. The total phenolic content in fruits estimated as gallic acid equivalent (GAE) ranged from 2.64 mg per g dry weight (DW) for kiwifruit to 90.64 mg per g GAE for walnut. The highest antioxidant activity was observed in rose hip as 92.31 %, while the lowest was in orange (32.43 %), respectively. The antioxidant activity of butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) were found 90.7 and 89.9 %, respectively. There was no correlation (R = 0.788) between total phenolic content and antioxidant activity among species. The results indicate the presence of significant antioxidant activity, which strongly affected by species in fruit families.